2009
DOI: 10.1002/jbm.a.32577
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells: Influence of oxygen pressure on proliferation and chondrogenic differentiation in fibrin glue in vitro

Abstract: Tissue engineering using biomaterials is a promising solution for cartilage replacement. The purpose of this study was to investigate whether the fibrin sealant Tissucol(R) provides a suitable scaffold for re-implanting stem cells during chondrogenic replacement therapy. Pluripotent stem cells were isolated from adult human bone marrow (hMSCs), cultured and characterized by FACS (CD105+/CD106+, CD45-/CD14-/CD34-). A large-holed porous hMSC-containing fibrin matrix was built that allowed hMSCs to survive throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…Treatment with GDF5/Dex showed similar effects, although with different collagen to aggrecan ratios, while hypoxic conditions generally enhanced the chondrogenic response. These benefi cial effects of low oxygen tension in terms of chondrogenic or NP-like differentiation of MSCs are in agreement with previously described data and are likely to refl ect the in vivo situation that is characterised by physiologically low oxygen concentration in NP and cartilaginous tissues (Risbud et al, 2004;Baumgartner et al, 2010;Markway et al, 2010).…”
Section: Matrix and Marker Protein Accumulationsupporting
confidence: 89%
See 1 more Smart Citation
“…Treatment with GDF5/Dex showed similar effects, although with different collagen to aggrecan ratios, while hypoxic conditions generally enhanced the chondrogenic response. These benefi cial effects of low oxygen tension in terms of chondrogenic or NP-like differentiation of MSCs are in agreement with previously described data and are likely to refl ect the in vivo situation that is characterised by physiologically low oxygen concentration in NP and cartilaginous tissues (Risbud et al, 2004;Baumgartner et al, 2010;Markway et al, 2010).…”
Section: Matrix and Marker Protein Accumulationsupporting
confidence: 89%
“…In the present study we measured the influence of hypoxia on human bone marrow derived MSCs in three dimensional alginate cultures as a modulator of the effects of transforming growth factor beta 1 (TGFβ1), GDF5 and coculture with bovine nucleus pulposus cells (bNPC), for the purpose of inducing an IVD-like phenotype. Hypoxic conditions applying 2 % oxygen tension were chosen to mimic the avascular hypoxic environment of the NP tissue; previous studies had shown enhanced chondrogenic and NP-like differentiation in MSCs cultured under 2-3 % oxygen (Risbud et al, 2004;Felka et al, 2009;Baumgartner et al, 2010;Markway et al, 2010). We hypothesised that different combinations of hypoxia with growth factors or coculture may have synergistic or modulatory effects and some of these combinations may result in a differentiation pattern approaching that of IVD cells.…”
Section: Role Of Hypoxia and Growth And Differentiation Factor-5 On Dmentioning
confidence: 99%
“…Furthermore, the high volumetric stress environment of the IVD could direct MSC differentiation towards a chondrogenic phenotype [16,94]. Hypoxia has been shown to impair adipogenesis and osteogenesis of human MSCs [38], and as a potent chondrogenesis promoter than dynamic compression or hydrostatic pressure in the presence of transforming growth factor b (TGF-b) [7,74,77,105]. Nevertheless, low oxygen tension and hydrostatic pressure alone without TGF-b could not initiate chondrogenesis of MSC [105].…”
Section: Ivd Tissue Engineeringmentioning
confidence: 99%
“…Particular interest was demonstrated in the use of specific media to support proliferation by MSCs and their transdifferentiation process. Some studies showed that hypoxia can induce chondrogenesis and chondrogenic differentiation of MSCs [62][63][64]. Further reports highlighted the use of a bioreactor with co-culture of MSCs and other stem cells to study the culture and mechanical stimulation [65].…”
Section: Discussionmentioning
confidence: 99%